A transgenic mouse model of human T cell leukemia virus type 1-associated diseases - Ohsugi, Takeo (Frontiers in Microbiology, 2013)
Human T-cell leukemia virus type I (HTLV-1) is the etiological agent of adult T-cell leukemia/lymphoma (ATLL) and several inflammatory diseases. Tax, the protein encoded by HTLV-1, may be responsible for the development of the diseases caused by this virus. To investigate the pathogenic role of Tax, several transgenic mouse strains expressing Tax have been developed in recent years. These mice develop various tumors including large granular lymphocytic leukemia, as well as inflammatory diseases such as arthritis. These results suggest that Tax expression alone is sufficient to cause both malignant neoplastic diseases and inflammatory diseases. However, until recently, there were no tax transgenic mice that develop T-cell leukemia and lymphoma resembling ATLL. The first successful induction of leukemia in T cells was pre–T-cell leukemia generated in transgenic mice in which a mouse lymphocyte-specific protein tyrosine kinase p56lck (lck) proximal promoter was used to express the tax gene in immature T cells. Subsequently, transgenic mice were established in which the lck-distal promoter was used to express Tax in mature T cells; these mice developed mature T-cell leukemia and lymphoma that more closely resembled ATLL than did earlier mouse models.